Independência financeira e a emancipação de distritos no Estado do Ceará - Oliveira, Alexandre Nunes de (2014)
The present work search investigate the chance of financial involution among the Cearenses' municipalities, from accounting data for 150 localities in periods of 2004, 2008 and 2012. The sample comprises 82% of the total number of municipalities in the state of Ceará and the method used follows a binary dependent variable model, with Probit's hypothesis. The econometric model proposed considered variables of financial autonomy,dependence on transfers, personnel expenses and charges, education expenses and health expenses. The estimates leads us to conclude that the chance is significant in that a new municipality that will be created has fundraising less than the average, being considered a economic-financial scenario unfavorable the process of emancipation of districts in the state of Ceará, there is a view that the Cearenses' municipalities are considered to be poor and highly dependent on features of transfers.